The Curious Incident of the Dog in the Night-Time - Haddon, Mark. (London : Vintage, 2004)
A murder mystery like no other, this novel features Christopher Boone, a 15 year-old who suffers from Asperger's syndrome. When he finds a neighbour's dog murdered, he sets out on a journey which will turn his whole world upside down.
Originally published: London: Jonathan Cape, 2003.
Accelerated Reader/Renaissance Learning
Whitbread Novel of the Year Award
Keywords: Asperger's syndrome -- Patients -- Fiction; Puzzles -- Fiction